2000
DOI: 10.1109/16.853034
|View full text |Cite
|
Sign up to set email alerts
|

Super thin-film transistor with SOI CMOS performance formed by a novel grain enhancement method

Abstract: High performance super TFT's with different channel widths and lengths, formed by a novel grain enhancement method, are reported. High temperature annealing has been utilized to enhance the polysilicon grain and improve the quality of silicon crystal after low temperature MILC treatment on amorphous silicon. With device scaling, it is possible to fabricate the entire transistor on a single grain, thus giving the performance of single crystal SOI MOSFET. The effects of grain boundaries on device performance hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…7,8 The conventional solid phase crystallization ͑SPC͒ process spends several dozen hours at around 600°C to obtain defect-rich polysilicon films; 9 by contrast the Ni-MILC process occurs at lower temperatures, ranging from 450 to 550°C, and gives larger crystalline grains with improved electrical characteristics. 7 It is also reported that polysilicon TFTs fabricated by the combination of Ni-MILC process and subsequent annealing at 900°C for 30 min exhibit high electron mobility of 430 cm 2 V Ϫ1 s Ϫ1 .…”
mentioning
confidence: 99%
“…7,8 The conventional solid phase crystallization ͑SPC͒ process spends several dozen hours at around 600°C to obtain defect-rich polysilicon films; 9 by contrast the Ni-MILC process occurs at lower temperatures, ranging from 450 to 550°C, and gives larger crystalline grains with improved electrical characteristics. 7 It is also reported that polysilicon TFTs fabricated by the combination of Ni-MILC process and subsequent annealing at 900°C for 30 min exhibit high electron mobility of 430 cm 2 V Ϫ1 s Ϫ1 .…”
mentioning
confidence: 99%
“…They were acting as buried oxide, active layer and sacrificial oxide, respectively. In this work, the metal-induced lateral crystallization (MILC) technology with nickel as catalyst was used to recrystallize the amorphous silicon film to poly-Si film at low temperature [11], as shown in Figure 1(a). The inducing windows for the MILC process were opened on the sacrificial LTO layer using conventional photolithography and wet etch.…”
Section: Device Fabricationmentioning
confidence: 99%
“…However, this process is required with high-temperature (~723 K) annealing. In SPC process, Si ion implantation [7] and deposition of metal on the a-Si [8] are increasing the crystal nucleation in the film. Metal-induced crystallization (MIC) technique, that is one of SPC method, is a method for obtaining polycrystalline of large grain size at extremely lowtemperature on insulating substrate [9].…”
Section: Introductionmentioning
confidence: 99%